Stable refugial environment for Late Pleistocene fauna in southern Peloponnese, Greece: Insights from enamel isotopes of ruminants - Marianthi Tzortzi; Federico Lugli; Vasilis Golfinopoulos; Daniel Green; Elena Armaroli; George Iliopoulos; Thomas Tütken; Hubert Vonhof; Andreas Darlas (Quaternary Science Reviews, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Experimental assessment of ambient gamma dose equivalent rates measured outdoors in the Republic of Benin from 2019 to 2020 - Arnaud A. Gbetchedji; Daniel S. Takou; N. Innocent Gbaï; Mahougnon B. Zinsou; Hubert C. Hounsossou; Thierry C. M. Medehouenou; Rodrigue S. Allodji (Environmental Monitoring and Assessment, 2026)

Eemian climate seasonality reconstructed from intra-tooth oxygen, carbon, and nitrogen stable isotopes in equid enamel from Neumark-Nord 2, Germany - Marissa Vink; Jennifer N. Leichliter; Daniel R. Green; Sven Brömme; Théo Tacail; Lutz Kindler; Wil Roebroeks; Sabine Gaudzinski-Windheuser; Gerald H. Haug; Hubert B. Vonhof; Alfredo Martínez-García; Thomas Tütken; et al. (Quaternary Science Reviews, 2026)

Diachronic reconstruction of palaeoclimates and diet through stable isotopes (δ13C and δ18O) and 2D geometric morphometrics from cave bear (Ursus spelaeus) dentition - Daniel Charters; Hubert B. Vonhof; Richard P. Brown; Dominique Bonjean; Isabelle De Groote; Carolin Pellio; Grégory Abrams; Carlo Meloro (Quaternary International, 2025)

Full-Resolution Sentinel-3 Satellite Observations of Phytoplankton Phenology in Optically Complex Waters of the Northern Patagonian Shelf - Maximiliano Arena; Paula Pratolongo; Hubert Loisel; Manh Duy Tran; Daniel S. F. Jorge; Ana Laura Delgado (Estuaries and Coasts, 2025)
In this study, we characterized phytoplankton biomass variability in El Rincón, a shallow and biologically productive coastal region in the Patagonian Continental Shelf. We used as a proxy 7 years (2017–2024) of high-resolution Sentinel-3 OLCI satellite data to capture the fine scale spatio-temporal variability of Chl- a in this region. To obtain Chl- a concentration, we applied a regionally validated algorithm (MuRB&NDCI) which provides more accurate Chl- a estimates compared to traditional algorithms, particularly in optically complex waters. Self-organizing maps (SOM) neural network was applied to identify four distinct bio-geographical regions with unique bloom dynamics. The phenological estimates revealed that phytoplankton blooms typically initiate in fall (March), peak during winter (May–August), and are more pronounced near the Bahía Blanca Estuary (BBE), where nutrient and sediment inputs drive high productivity. The findings presented in this work highlight the utility of Optical Water Class–based algorithms for capturing the fine-scale spatiotemporal variability of Chl- a in coastal systems. This study advances our understanding of phytoplankton dynamics in El Rincón and underscores the importance of customized satellite-derived approaches for monitoring and managing productivity in shallow coastal environments.

Innovatives Bemessungsverfahren für Stauanlagen unter Anwendung von Johnson-Verteilungen - Hubert Lohr; Isabelle Huber; Sandra Richter; Gerd Demny; Daniel Bittner (WASSERWIRTSCHAFT, 2025)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Wnt7a Decreases Brain Endothelial Barrier Function Via β-Catenin Activation - Narek Manukjan; Steven Chau; Florian Caiment; Marcel van Herwijnen; Hubert J. Smeets; Daniel Fulton; Zubair Ahmed; W. Matthijs Blankesteijn; Sébastien Foulquier (Molecular Neurobiology, 2024)
The blood-brain barrier consists of tightly connected endothelial cells protecting the brain’s microenvironment from the periphery. These endothelial cells are characterized by specific tight junction proteins such as Claudin-5 and Occludin, forming the endothelial barrier. Disrupting these cells might lead to blood-brain barrier dysfunction. The Wnt/β-catenin signaling pathway can regulate the expression of these tight junction proteins and subsequent barrier permeability. The aim of this study was to investigate the in vitro effects of Wnt7a mediated β-catenin signaling on endothelial barrier integrity. Mouse brain endothelial cells, bEnd.3, were treated with recombinant Wnt7a protein or XAV939, a selective inhibitor of Wnt/β-catenin mediated transcription to modulate the Wnt signaling pathway. The involvement of Wnt/HIF1α signaling was investigated by inhibiting Hif1α signaling with Hif1α siRNA. Wnt7a stimulation led to activation and nuclear translocation of β-catenin, which was inhibited by XAV939. Wnt7a stimulation decreased Claudin-5 expression mediated by β-catenin and decreased endothelial barrier formation. Wnt7a increased Hif1α and Vegfa expression mediated by β-catenin. However, Hif1α signaling pathway did not regulate tight junction proteins Claudin-5 and Occludin. Our data suggest that Wnt7a stimulation leads to a decrease in tight junction proteins mediated by the nuclear translocation of β-catenin, which hampers proper endothelial barrier formation. This process might be crucial in initiating endothelial cell proliferation and angiogenesis. Although HIF1α did not modulate the expression of tight junction proteins, it might play a role in brain angiogenesis and underlie pathogenic mechanisms in Wnt/HIF1α signaling in diseases such as cerebral small vessel disease.

Tracing the fate of seabird‐derived nitrogen in a coral reef using nitrate and coral skeleton nitrogen isotopes - Noémie Choisnard; Nicolas Noel Duprey; Tanja Wald; Martin Thibault; Fanny Houlbrèque; Alan D. Foreman; Pascale Cuet; Mireille M. M. Guillaume; Hubert Vonhof; Daniel M. Sigman; Gerald H. Haug; Jean‐François Maguer; et al. (Limnology and Oceanography, 2024)
Seabirds transfer nutrients from the ocean to their nesting island, potentially altering nitrogen (N) cycling within adjacent terrestrial and marine ecosystems. Yet, the processes involved in seabird‐N transfer along the land–sea continuum remain elusive. Using δ 15 N and δ 18 O measurements of groundwater nitrate, we demonstrate the role of brackish groundwater located within a coral island's landmass as a major reservoir of nitrate (at millimolar levels). Nearly all of the total dissolved seabird‐derived N leaching into the groundwater (mostly ammonium and uric acid) is converted to nitrate by nitrification, as supported by the relatively low δ 18 O of the groundwater nitrate (3.97‰ ± 0.30‰). Comparison of nitrate δ 15 N and δ 18 O suggests that little denitrification takes place within the groundwater lens, implying that the high δ 15 N of groundwater nitrate (13.73‰ ± 0.05‰) derives from the high trophic position of seabirds and postdepositional processes that increase the δ 15 N of seabird excreta. Seawater and coral skeleton samples from a reef flat exposed to groundwater had higher δ 15 N values than at sites devoid of groundwater influence, indicating that the main source of N at the latter site was the Subtropical Upper Water, while the groundwater nitrate dominated the exposed reef flat N pool up to 200 m from shore. In addition, these results indicate that coral‐bound δ 15 N can detect seabird‐derived nitrate δ 15 N, raising opportunities to reconstruct historical seabird‐N inputs to coral reefs in relation to climatic and other changes, such as the introduction of invasive species.

Mapping tropical forest degradation with deep learning and Planet NICFI data - Ricardo Dalagnol; Fabien Hubert Wagner; Lênio Soares Galvão; Daniel Braga; Fiona Osborn; Le Bienfaiteur Sagang; Polyanna da Conceição Bispo; Matthew Payne; Celso Silva Junior; Samuel Favrichon; Vinicius Silgueiro; Liana O. Anderson; et al. (Remote Sensing of Environment, 2023)

Multi-year seabed environmental baseline in deep-sea offshore oil prospective areas established using microbial biodiversity - Deidra K. Ferguson; Carmen Li; Anirban Chakraborty; Daniel A. Gittins; Martin Fowler; Jamie Webb; Calvin Campbell; Natasha Morrison; Adam MacDonald; Casey R.J. Hubert (Marine Pollution Bulletin, 2023)

Public clay pot waters: a hidden risk for diarrheal diseases transmission in a cholera endemic area of Cameroon - Moussa Djaouda; Mireille Ebiane Nougang; Jean Dékouché Ldingté; Frédérique Demgodéré Thélé; Roméo Bouba Wakayansam; Daniel Amani Dawaye; Serge Hubert Zébazé Togouet; Song Liang; Moïse Nola (Sustainable Water Resources Management, 2023)

Assessment of the impacts of selected physicochemical and bacteriological parameters of wastewater (hospital effluents) from the University teaching hospital of Butare on the surrounding environment - Jean Baptiste Baranyika; Justin Katabarwa; Daniel Kalisa Nyirimbibi; Serge Bakire; Hubert Hirwa (Journal of Cleaner Production, 2023)

Ocean color algorithm for the retrieval of the particle size distribution and carbon-based phytoplankton size classes using a two-component coated-sphere backscattering model - Tihomir S. Kostadinov; Lisl Robertson Lain; Christina Eunjin Kong; Xiaodong Zhang; Stéphane Maritorena; Stewart Bernard; Hubert Loisel; Daniel S. F. Jorge; Ekaterina Kochetkova; Shovonlal Roy; Bror Jonsson; Victor Martinez-Vicente; et al. (Ocean Science, 2023)
The particle size distribution (PSD) of suspended particles in near-surface seawater is a key property linking biogeochemical and ecosystem characteristics with optical properties that affect ocean color remote sensing. Phytoplankton size affects their physiological characteristics and ecosystem and biogeochemical roles, e.g., in the biological carbon pump, which has an important role in the global carbon cycle and thus climate. It is thus important to develop capabilities for measurement and predictive understanding of the structure and function of oceanic ecosystems, including the PSD, phytoplankton size classes (PSCs), and phytoplankton functional types (PFTs). Here, we present an ocean color satellite algorithm for the retrieval of the parameters of an assumed power-law PSD. The forward optical model considers two distinct particle populations: phytoplankton and non-algal particles (NAPs). Phytoplankton are modeled as coated spheres following the Equivalent Algal Populations (EAP) framework, and NAPs are modeled as homogeneous spheres. The forward model uses Mie and Aden–Kerker scattering computations, for homogeneous and coated spheres, respectively, to model the total particulate spectral backscattering coefficient as the sum of phytoplankton and NAP backscattering. The PSD retrieval is achieved via spectral angle mapping (SAM), which uses backscattering end-members created by the forward model. The PSD is used to retrieve size-partitioned absolute and fractional phytoplankton carbon concentrations (i.e., carbon-based PSCs), as well as particulate organic carbon (POC), using allometric coefficients. This model formulation also allows the estimation of chlorophyll a concentration via the retrieved PSD, as well as percent of backscattering due to NAPs vs. phytoplankton. The PSD algorithm is operationally applied to the merged Ocean Colour Climate Change Initiative (OC-CCI) v5.0 ocean color data set. Results of an initial validation effort are also presented using PSD, POC, and picophytoplankton carbon in situ measurements. Validation results indicate the need for an empirical tuning for the absolute phytoplankton carbon concentrations; however these results and comparison with other phytoplankton carbon algorithms are ambiguous as to the need for the tuning. The latter finding illustrates the continued need for high-quality, consistent, large global data sets of PSD, phytoplankton carbon, and related variables to facilitate future algorithm improvements.

Elevated bacterial endospores associated with thermogenic hydrocarbon seeps in deep sea sediments - Jayne E. Rattray; Gretta Elizondo; Kathryn Sloan; Natasha Morrison; Martin Fowler; Daniel A. Gittins; Jamie Webb; D. Calvin Campbell; Adam MacDonald; Casey R.J. Hubert (Organic Geochemistry, 2023)

Identification of virus infections of European eels intended for stocking measures - Linna Danne; Mikolaj Adamek; Hubert Wonnemann; Theresa Pieper; Daniel Fey; John Hellmann (Journal of Fish Diseases, 2022)
The spread of viral diseases in eels is suggested to severely affect the European eel ( Anguilla anguilla ) panmictic population. The European Commission has initiated the Eel Recovery Plan (Council Regulation No. 1100/2007) to try to return the European eel stock to more sustainable levels within that measures eel restocking. However, scientific evidence evaluating the efficacy of stocking remains scarce. In addition, knowledge about the impact and contribution of eel stocking on the distribution of infectious diseases is insufficient. In this study, we aimed to investigate virus infections in batches of eels intended for restocking. We analysed samples of glass eels from certified fisheries and farmed European eels from different aquaculture farms. All analysed eels were purchased within a North Rhine Westphalian conservation program. Via a combination of cell culture and qPCR‐based techniques, we detected infections of glass eels with the rhabdovirus Eel Virus European X and anguillid herpesvirus 1 infections in farmed eels (10–15 cm).

Sodium retention in nephrotic syndrome is independent of the activation of the membrane-anchored serine protease prostasin (CAP1/PRSS8) and its enzymatic activity - Daniel Essigke; Bernhard N. Bohnert; Andrea Janessa; Matthias Wörn; Kingsley Omage; Hubert Kalbacher; Andreas L. Birkenfeld; Thomas H. Bugge; Roman Szabo; Ferruh Artunc (Pflügers Archiv - European Journal of Physiology, 2022)
Experimental nephrotic syndrome leads to activation of the epithelial sodium channel (ENaC) by proteolysis and promotes renal sodium retention. The membrane-anchored serine protease prostasin (CAP1/PRSS8) is expressed in the distal nephron and participates in proteolytic ENaC regulation by serving as a scaffold for other serine proteases. However, it is unknown whether prostasin is also involved in ENaC-mediated sodium retention of experimental nephrotic syndrome. In this study, we used genetically modified knock-in mice with Prss8 mutations abolishing its proteolytic activity (Prss8-S238A) or prostasin activation (Prss8-R44Q) to investigate the development of sodium retention in doxorubicin-induced nephrotic syndrome. Healthy Prss8-S238A and Prss8-R44Q mice had normal ENaC activity as reflected by the natriuretic response to the ENaC blocker triamterene. After doxorubicin injection, all genotypes developed similar proteinuria. In all genotypes, urinary prostasin excretion increased while renal expression was not altered. In nephrotic mice of all genotypes, triamterene response was similarly increased, consistent with ENaC activation. As a consequence, urinary sodium excretion dropped in all genotypes and mice similarly gained body weight by + 25 ± 3% in Prss8-wt, + 20 ± 2% in Prss8-S238A and + 28 ± 3% in Prss8-R44Q mice ( p = 0.16). In Western blots, expression of fully cleaved α- and γ-ENaC was similarly increased in nephrotic mice of all genotypes. In conclusion, proteolytic ENaC activation and sodium retention in experimental nephrotic syndrome are independent of the activation of prostasin and its enzymatic activity and are consistent with the action of aberrantly filtered serine proteases or proteasuria.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Regionwide temporal gradients of carbon allocation allow for shoot growth and latewood formation in boreal black spruce - Valentina Buttò; Siddhartha Khare; Guillaume Drolet; Jean‐Daniel Sylvain; Fabio Gennaretti; Annie Deslauriers; Hubert Morin; Sergio Rossi (Global Ecology and Biogeography, 2021)
Aim In boreal ecosystems, phenological events display seasonal patterns. These patterns allow for the development of tissues during the short time window available for growth in cold climates. Primary and secondary growth, two expensive processes for plants, are supposedly modulated in time to optimize allocation of carbon to bud and woody tissues. We aimed to assess the phenology of primary and secondary meristems, testing their relationship over the closed black spruce stands of the commercially exploited forest region in Quebec, Canada. Location Quebec, Canada. Time period 2002–2016. Major taxa studied Gymnospermae. Methods We combined weekly scaled field observations with Moderate Resolution Imaging Spectroradiometer (MODIS) time series of the normalized difference vegetation index (NDVI) to extract timings of photosynthesis and meristem growth in five black spruce [ Picea mariana (Mill.) B.S.P.] stands located along a latitudinal gradient and to assess their relationship. We then tested empirical models based on geographical position and seasonal temperatures to predict wood phenology (i.e., the onset and ending of earlywood and latewood formation), and compared its spatial patterns with existing predictions of bud phenology for the same study area. Results Photosynthesis started at the beginning of May, 3 weeks before bud reactivation and the onset of wood growth. Latewood formation started in mid‐July, after shoot elongation was completed. For wood phenology models, the residual standard error ranged from 1 week to 12 days. Growth dynamics spatialized across the boreal forest of Quebec varied with the transition between the subarctic and humid continental climate. Main conclusions Shoot elongation and latewood formation were temporally separated, providing evidence of a trade‐off in structural carbon allocation between primary and secondary growth in trees. Spatial patterns of wood phenology predicted for the black spruce polygons are consistent with spatial patterns of bud phenology, demonstrating synchronized temporal dynamics of meristems at the regional scale.

Antibiotic consumption in developing countries defies global commitments: an overview on Brazilian growth in consumption - Paulo Bernardo Neves e Castro; Daniel Aparecido da Silva Rodrigues; Hubert Mathias Peter Roeser; Aníbal da Fonseca Santiago; Robson José de Cássia Franco Afonso (Environmental Science and Pollution Research, 2020)

Megacity development and the demise of coastal coral communities: Evidence from coral skeleton δ 15 N records in the Pearl River estuary - Nicolas N. Duprey; Tony X. Wang; Taihun Kim; Jonathan D. Cybulski; Hubert B. Vonhof; Paul J. Crutzen; Gerald H. Haug; Daniel M. Sigman; Alfredo Martínez‐García; David M. Baker (Global Change Biology, 2020)
Historical coral skeleton (CS) δ 18 O and δ 15 N records were produced from samples recovered from sedimentary deposits, held in natural history museum collections, and cored into modern coral heads. These records were used to assess the influence of global warming and regional eutrophication, respectively, on the decline of coastal coral communities following the development of the Pearl River Delta (PRD) megacity, China. We find that, until 2007, ocean warming was not a major threat to coral communities in the Pearl River estuary; instead, nitrogen (N) inputs dominated impacts. The high but stable CS‐δ 15 N values (9‰–12‰ vs. air) observed from the mid‐Holocene until 1980 indicate that soil and stream denitrification reduced and modulated the hydrologic inputs of N, blunting the rise in coastal N sources during the early phase of the Pearl River estuary urbanization. However, an unprecedented CS‐δ 15 N peak was observed from 1987 to 1993 (>13‰ vs. air), concomitant to an increase of NH 4 + concentration, consistent with the rapid Pearl River estuary urbanization as the main cause for this eutrophication event. We suggest that widespread discharge of domestic sewage entered directly into the estuary, preventing removal by natural denitrification hotspots. We argue that this event caused the dramatic decline of the Pearl River estuary coral communities reported from 1980 to 2000. Subsequently, the coral record shows that the implementation of improved wastewater management policies succeeded in bringing down both CS‐δ 15 N and NH 4 + concentrations in the early 2000s. This study points to the potential importance of eutrophication over ocean warming in coral decline along urbanized coastlines and in particular in the vicinity of megacities.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Revisiting species boundaries and distribution ranges of Nemacheilus spp. (Cypriniformes: Nemacheilidae) and Rasbora spp. (Cypriniformes: Cyprinidae) in Java, Bali and Lombok through DNA barcodes: implications for conservation in a biodiversity hotspot - Nicolas Hubert; Daniel Lumbantobing; Arni Sholihah; Hadi Dahruddin; Erwan Delrieu-Trottin; Frédéric Busson; Sopian Sauri; Renny Hadiaty; Philippe Keith (Conservation Genetics, 2019)

Das Mikromilieu beeinflusst das Zellschicksal von Keimzelltumoren - Daniel Nettersheim; Hubert Schorle (BIOspektrum, 2017)

Transcriptional profiling by RNA sequencing of black pepper (Piper nigrum L.) roots infected by Fusarium solani f. sp. piperis - Edith C. O. Moreira; Daniel G. Pinheiro; Sheila M. C. Gordo; Simone M. Rodrigues; Elaine Pessoa; Hubert Schaller; Oriel F. de Lemos; Artur Silva; Horacio Schneider; Wilson A. Silva; Iracilda Sampaio; Sylvain Darnet (Acta Physiologiae Plantarum, 2017)

Climate‐induced changes in host tree–insect phenology may drive ecological state‐shift in boreal forests - Deepa S. Pureswaran; Louis De Grandpré; David Paré; Anthony Taylor; Martin Barrette; Hubert Morin; Jacques Régnière; Daniel D. Kneeshaw (Ecology, 2015)
Climate change is altering insect disturbance regimes via temperature‐mediated phenological changes and trophic interactions among host trees, herbivorous insects, and their natural enemies in boreal forests. Range expansion and increase in outbreak severity of forest insects are occurring in Europe and North America. The degree to which northern forest ecosystems are resilient to novel disturbance regimes will have direct consequences for the provisioning of goods and services from these forests and for long‐term forest management planning. Among major ecological disturbance agents in the boreal forests of North America is a tortricid moth, the eastern spruce budworm, which defoliates fir ( Abies spp.) and spruce ( Picea spp.). Northern expansion of this defoliator in eastern North America and climate‐induced narrowing of the phenological mismatch between the insect and its secondary host, black spruce ( Picea mariana ), may permit greater defoliation and mortality in extensive northern black spruce forests. Although spruce budworm outbreak centers have appeared in the boreal black spruce zone historically, defoliation and mortality were minor. Potential increases in outbreak severity and tree mortality raise concerns about the future state of this northern ecosystem. Severe spruce budworm outbreaks could decrease stand productivity compared with their occurrence in more diverse, southern balsam fir forest landscapes that have coevolved with outbreaks. Furthermore, depending on the proportion of balsam fir and deciduous species present and fire recurrence, changes in regeneration patterns and in nutrient cycling could alter ecosystem dynamics and replace black spruce by more productive mixed‐wood forest, or by less productive ericaceous shrublands. Long‐term monitoring, manipulative experiments, and process modeling of climate‐induced phenological changes on herbivorous insect pests, their host tree species, and natural enemies in northern forests are therefore crucial to predicting species range shifts and assessing ecological and economic impacts.

Combined effects of climate, resource availability, and plant traits on biomass produced in a Mediterranean rangeland - Simon Chollet; Serge Rambal; Adeline Fayolle; Daniel Hubert; Didier Foulquié; Eric Garnier (Ecology, 2014)
Biomass production in grasslands, a key component of food provision for domestic herbivores, is known to depend on climate, resource availability, and on the functional characteristics of communities. However, the combined effects of these different factors remain largely unknown. The aim of the present study was to unravel the causes of variations in the standing biomass of plant communities using a long‐term experiment conducted in a Mediterranean rangeland of Southern France. Two management regimes, sheep grazing and grazing associated with mineral fertilization, were applied to different areas of the study site over the past 25 years. Abiotic (temperature, available water, nutrients) and biotic (components of the functional structure communities) factors were considered to explain interannual and spatial variations in standing biomass in these rangelands. Standing biomass was highly predictable, with the best model explaining ∼80% of variations in the amount of biomass produced, but the variation explained by abiotic and biotic factors was dependent on the season and on the management regime. Abiotic factors were found to have comparable effects in both management regimes: The amount of biomass produced in the spring was limited by cold temperatures, while it was limited by water availability and high temperatures in the summer. In the fertilized community, the progressive change in the functional structure of the communities had significant effects on the amount of biomass produced: the dominance of few productive species which were functionally close led to higher peak standing biomass in spring.

A three-year increase in soil temperature and atmospheric N deposition has minor effects on the xylogenesis of mature balsam fir - Loïc D’Orangeville; Benoît Côté; Daniel Houle; Hubert Morin; Louis Duchesne (Trees, 2013)

89Zr-Labeled Paramagnetic Octreotide-Liposomes for PET-MR Imaging of Cancer - Diane S. Abou; Daniel L. J. Thorek; Nicholas N. Ramos; Martijn W. H. Pinkse; Hubert T. Wolterbeek; Sean D. Carlin; Bradley J. Beattie; Jason S. Lewis (Pharmaceutical Research, 2013)

A study on hydrological series of the Niger River - Tommaso Abrate; Pierre Hubert; Daniel Sighomnou (Hydrological Sciences Journal, 2013)

Aldehyde dehydrogenase (ALDH) superfamily in plants: gene nomenclature and comparative genomics - Chad Brocker; Melpomene Vasiliou; Sarah Carpenter; Christopher Carpenter; Yucheng Zhang; Xiping Wang; Simeon O. Kotchoni; Andrew J. Wood; Hans-Hubert Kirch; David Kopečný; Daniel W. Nebert; Vasilis Vasiliou (Planta, 2013)

Population density and phenotypic attributes influence the level of nematode parasitism in roe deer - Guillaume Body; Hubert Ferté; Jean-Michel Gaillard; Daniel Delorme; François Klein; Emmanuelle Gilot-Fromont (Oecologia, 2011)

Development and Experimental Validation of a 20K Atlantic Cod (Gadus morhua) Oligonucleotide Microarray Based on a Collection of over 150,000 ESTs - Marije Booman; Tudor Borza; Charles Y. Feng; Tiago S. Hori; Brent Higgins; Adrian Culf; Daniel Léger; Ian C. Chute; Anissa Belkaid; Marlies Rise; A. Kurt Gamperl; Sophie Hubert; et al. (Marine Biotechnology, 2011)

Inhibitory network of spiking neurons may express a sharp peak of synchrony at low frequency band - Pierre Meyrand; Daniel Cattaert; Hubert Ostaszewski; Tiaza Bem (Biological Cybernetics, 2009)

Prnp knockdown in transgenic mice using RNA interference - Micaela Gallozzi; Jérome Chapuis; Fabienne Le Provost; Annick Le Dur; Caroline Morgenthaler; Coralie Peyre; Nathalie Daniel-Carlier; Eric Pailhoux; Marthe Vilotte; Bruno Passet; Laetitia Herzog; Vincent Beringue; et al. (Transgenic Research, 2008)

Relationship between I?B? deficiency, NF?B activity and interleukin-8 production in CF human airway epithelial cells - Olivier Tabary; Sandie Escotte; Jean Couetil; Dominique Hubert; Daniel Dusser; Edith Puchelle; Jacky Jacquot (Pflügers Archiv - European Journal of Physiology, 2001)

Yield response of Lolium perenne swards to free air CO 2 enrichment increased over six years in a high N input system on fertile soil - Markus Daepp; Daniel Suter; José P. F. Almeida; Hubert Isopp; Ueli A. Hartwig; Marco Frehner; Herbert Blum; Josef Nösberger; Andreas Lüscher (Global Change Biology, 2000)
Summary After a step increase in the atmospheric partial pressure of CO 2 (pCO 2 ), the availability of mineral N may be insufficient to meet the plant's increased demand for N. Over time, however, the ecosystem may adapt to the new conditions, and a new equilibrium may be established in the fluxes of C and N. This would result in a higher dry mass (DM) yield response of the plants to elevated pCO 2 . The effect of elevated atmospheric pCO 2 (60 Pa pCO 2 ) was studied in Lolium perenne L. swards with two N fertilization treatments (14 and 56 g m −2 y −1 ) in a six‐year FACE (Free Air Carbon dioxide Enrichment) experiment. In the high N treatment, the input of N with fertilizer considerably exceeded the export of N with the harvested plant material in both CO 2 treatments leading to an apparent net input of N into the ecosystem. Accordingly, the proportion of harvested N derived from 15 N labelled fertilizer N, applied throughout the experiment ( Lolium perenne sward to elevated pCO 2 increased (from 7% in 1993 to 25% in 1998). In parallel, the response of N yield to elevated pCO 2 increased, and the initially negative effect of elevated pCO 2 on specific leaf area (SLA) disappeared. The high N input system seemed to overcome in part an initially limiting effect of N on the yield response to elevated pCO 2 within a few years. In contrast, there was no apparent net input of N into the ecosystem in the low N treatment, because N fertilization just compensated the export of N with the harvested plant material. Accordingly, the proportion of harvested N yield, derived from fertilizer N, which was applied throughout the experiment, remained low. At low N, the availability of mineral N strongly limited plant growth and yield production in both CO 2 treatments; the low yields of DM and N, the low concentration of N in the plant material, and the low SLA reflected this. Although the plants grew under the same environmental conditions and the same management treatment as plants in the high N treatment, the response of DM yields to elevated pCO 2 in the low N treatment remained weak throughout the experiment (5% in 1993 and 9% in 1998). The results are discussed in the context of the sizes of the different N pools in the soil, the allocation of N within the plant and the possible effects on temporal immobilization, and the availability of mineral N for yield production as affected by elevated pCO 2 and N fertilization.

Δ7-Sterol-C5-desaturase: molecular characterization and functional expression of wild-type and mutant alleles - Tania Husselstein; Hubert Schaller; Daniel Gachotte; Pierre Benveniste (Plant Molecular Biology, 1999)

Relationships between boron concentrations and trout in the firehole river, wyoming - Joseph S. Meyer; Ann M. Boelter; Daniel F. Woodward; Jack N. Goldstein; Aïda M. Farag; Wayne A. Hubert (Biological Trace Element Research, 1998)

Aquaporin-related proteins in the filter chamber of homopteran insects - Françoise Le Caherec; Marie-Thérèse Guillam; Fabienne Beuron; Annie Cavalier; Daniel Thomas; Jean Gouranton; Jean-François Hubert (Cell and Tissue Research, 1997)